2022
DOI: 10.1002/ps.7039
|View full text |Cite
|
Sign up to set email alerts
|

Colupulone, colupone and novel deoxycohumulone geranyl analogues as larvicidal agents against Culex pipiens

Abstract: BACKGROUND As climate change proceeds, the management of the population of mosquitoes becomes more and more challenging. Insect adulticides and larvicides constitute significant control techniques, with the latter being considered the leading mosquito control method. However, the development of mosquito resistance development and the adverse side effects caused by the extensive use of synthetic insecticides have turned research towards the discovery of environmentally‐friendly solutions. Plants and bacteria ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Osteoporosis (Wu et al, 2023), mood disorders (Bonnet et al, 2021) Colupulone analogs Larvicidal agents (Makri et al, 2022) Exosomes b AD (NCT04388982), COVID19 (Mitrani et al, 2021); craniofacial neuralgia (NCT04202783), depression (NCT04202770), cutaneous wound healing (NCT02565264), multiple organ dysfunction after surgical repair of acute aortic dissection (NCT04356300), dry eye in chronic host vs. graft disease (NCT04213248), type 1 diabetes (NCT02138331), metastatic pancreatic cancer (NCT03608631), diagnostic and prognostic biomarker analysis (Liu et al, 2018;Qin et al, 2020;Chang et al, 2021) Ketone bodies c AD (NCT04701957), heart failure (NCT05768100), type 2 diabetes (NCT03657537, NCT04854330, NCT05155410), multiple sclerosis (NCT03740295), cardiogenic shock (NCT04642768), alcohol use disorder (NCT04616781), McArdle disease (NCT03945370), Parkinson's disease and Lewy body dementia (NCT05778695), amyotrophic lateral sclerosis (ALS) (NCT02716662, NCT04820478), acute heart failure (NCT04442555, NCT05348460), eating disorders (NCT05507008), obesity (NCT03729934), polycystic ovary syndrome (NCT04163120), upper respiratory tract infections (NCT04019730), COVID-19 (NCT04573764), concussion (NCT04079907), aging (NCT06068803)…”
Section: Experimental Approachmentioning
confidence: 99%
“…Osteoporosis (Wu et al, 2023), mood disorders (Bonnet et al, 2021) Colupulone analogs Larvicidal agents (Makri et al, 2022) Exosomes b AD (NCT04388982), COVID19 (Mitrani et al, 2021); craniofacial neuralgia (NCT04202783), depression (NCT04202770), cutaneous wound healing (NCT02565264), multiple organ dysfunction after surgical repair of acute aortic dissection (NCT04356300), dry eye in chronic host vs. graft disease (NCT04213248), type 1 diabetes (NCT02138331), metastatic pancreatic cancer (NCT03608631), diagnostic and prognostic biomarker analysis (Liu et al, 2018;Qin et al, 2020;Chang et al, 2021) Ketone bodies c AD (NCT04701957), heart failure (NCT05768100), type 2 diabetes (NCT03657537, NCT04854330, NCT05155410), multiple sclerosis (NCT03740295), cardiogenic shock (NCT04642768), alcohol use disorder (NCT04616781), McArdle disease (NCT03945370), Parkinson's disease and Lewy body dementia (NCT05778695), amyotrophic lateral sclerosis (ALS) (NCT02716662, NCT04820478), acute heart failure (NCT04442555, NCT05348460), eating disorders (NCT05507008), obesity (NCT03729934), polycystic ovary syndrome (NCT04163120), upper respiratory tract infections (NCT04019730), COVID-19 (NCT04573764), concussion (NCT04079907), aging (NCT06068803)…”
Section: Experimental Approachmentioning
confidence: 99%
“…[11] Evgenia et al found that 4-aminopyrimidine-N-oxides exhibited anti-tickborne encephalitis virus (TBEV) effect. [12] On the other hand, natural products phloroglucinol and its derivatives show a broad range of activities such as antiviral, [13] antibacterial, [14] insecticidal [15] and anti-HSV activities. Su et al showed that phloroglucinol derivatives have good anti-HSV-1 effect in vitro.…”
Section: Introductionmentioning
confidence: 99%